2012
DOI: 10.1103/physrevb.86.014425
|View full text |Cite
|
Sign up to set email alerts
|

Co/Ni(111) superlattices studied by microscopy, x-ray absorption, andab initiocalculations

Abstract: We explore the origins of perpendicular magnetic anisotropy in epitaxial and textured Co/Ni (111) superlattices using a combination of thin film growth, structural characterization, x-ray magnetic circular dichroism (XMCD) and ab-initio calculations. Transmission electron microscopy and x-ray diffraction experiments allow us to show that the "bulk" magnetoelastic contribution to the total magnetic energy is small compared to the interface anisotropy. The magnetic properties are studied by using XMCD at the Co … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 94 publications
5
29
1
Order By: Relevance
“…5b is the high-resolution XPS survey spectrum of the Ni peaks. The observed binding energy of Ni 2p 3/2 at 852.0 eV and 855.2 eV indicated the deposited nickel compounds on the surface of CdS contained metallic Ni and NiO [28,29], which was consistent with TEM results. The high-resolution XPS spectrum of Ni of the sample CNR was shown in Fig.…”
Section: Tem and Xps Analysessupporting
confidence: 91%
“…5b is the high-resolution XPS survey spectrum of the Ni peaks. The observed binding energy of Ni 2p 3/2 at 852.0 eV and 855.2 eV indicated the deposited nickel compounds on the surface of CdS contained metallic Ni and NiO [28,29], which was consistent with TEM results. The high-resolution XPS spectrum of Ni of the sample CNR was shown in Fig.…”
Section: Tem and Xps Analysessupporting
confidence: 91%
“…Indeed, for both sample sets the roughness of the multilayered structures increases for increasing n. Therefore for our both sample sets, for decreasing trend of PMA with increasing n, the second explanation is valid. It was reported that MBE grown Co/Ni multilayers have a stronger PMA than sputtered Co/Ni multilayers due to more coherent growth [18,19]. However, there was no report about PMA of Co/Ni multilayers in which only the deposition method of Ni sublayers changed from sputtering to MBE.…”
Section: Resultsmentioning
confidence: 97%
“…Since H c ⊥ indicates the strength of PMA [22], the findings reveal that while even only Ni sub-layers are grown by MBE, a stronger PMA is obtained. The origin of PMA in Co/Ni multilayers is attributed to interface anisotropy in addition to bulk (111) magneto crystalline anisotropy [18]. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To verify this point, an experimental study on an epitaxial crystalline [Co/Ni] system with a welldefinedanisotropy axis [95] K are also of great interest in magnetic recording media since higher thermal stability can be achieved [97,98] for a given reversal field. In the future it is then of great interest to continue the characterization and the study of the origin of perpendicular magnetic anisotropy in thin film and multilayers [99][100][101].…”
Section: Origin Of the Symmetry Breakingmentioning
confidence: 99%